Semi C Fuzzy Operator. (December 2018) - Xavier, P.; Thangavelu, P.
Abstract: The link between open and closed sets in fuzzy topological space is well established by utilizing the classical complement C ( λ ) = 1 − λ . The concept of arbitrary complement function in fuzzy literature generalizes the concepts of fuzzy topological spaces. A new class of semi sets is proposed by arbitrary fuzzy complement and their properties are discussed.